Myrciaria dubia “Camu Camu” Fruit: Health-Promoting Phytochemicals and Functional Genomic Characteristics - Castro Gómez, Juan Carlos (2018)
Camu camu is a typical Amazon native fruit shrub that possesses a diploid genome, moderate genetic diversity, and population structure. The fruits accumulate several essential nutrients and synthesize L-ascorbic acid (vitamin C) in great quantities and an array of diverse secondary metabolites with corroborated in vitro and in vivo health-promoting activities. These beneficial effects include antioxidative and antiinflammatory activities, antiobesity, hypolipidemic, antihypertensive and antidiabetic effects, DNA damage and cancer protection effects, and other bioactivities. Many health-promoting phytochemicals are biosynthesized in several metabolic pathways of camu camu. Their reconstruction from the fruit transcriptome database was accomplished by our research group. These include basic metabolic pathways such as glycolysis and pentose phosphate pathway, vitamin C biosynthesis pathways, and pathways involved in secondary metabolites production. Due to their agronomic potential and fruits growing demand, recently, based on an ideotype, programs were initiated for their domestication and genetic improvement, but so far with very negligible achievements. Consequently, we propose new strategies to accelerate the processes of domestication and genetic improvement based on state of the art technologies for multiomic data analysis and innovative molecular tools.